English your way 2.0 immersion edition - Syracuse Language Systems (New York : Syracuse, 1997)
Complete interactive course for travel - business - students
Περιέχει ελληνικό βιβλίο οδηγιών; Αναγνώριση φωνής: ακούει και αξιολογεί την προφορά
System requirements: IBM PC or compatible PC; 486DX33 or faster microprocessor; Windows 3.1 or 95 operating system; 8MB of RAM; 16MB of hard drive space; SVGA 256-colors display; CD-ROM drive; 16 bit sound card; Speaker or headphones; Mouse; Microphone (for Speech Regognition and record/playback)
Keywords: English language -- Study and teaching -- CD-ROMs.; English language -- Self-instruction.; English language -- Computer-Assisted instruction; CD-ROMs.